Android Based Educational Game in Learning and Teaching English Vocabulary - Insani Nurchintyawati, S.Pd.,M.Pd (English Lecturers and Teachers Association (ELTA), 2022)
Vocabulary learning is often perceived as boring by learners, especially for those who grew up in the digital era. The use of online games in vocabulary learning and teaching can be one solution to solve this problem. Android is the current world-famous software nowadays. It is believed to help teachers in delivering knowledge effectively and efficiently. Therefore, this paper aims to illustrate the effectiveness of Android-based educational games to enhance the ability of learners in learning English vocabulary. The discussion includes overview about vocabulary, games, ICT tools in EFL classroom, and the use of educational games from Android (App Inventor) can improve students' English competence in learning vocabulary. Therefore, this paper will be explained about the use of Android-based educational games as one of the fun alternative teaching innovations to support creative teachers and students. And hopefully it can be useful and meaningful reference and information for the reader about the use of android based educational game in learning and teaching English Vocabulary. Keywords: Android based educational game, vocabulary, ICT tool.